Pertumbuhan Benih Ikan Betok (Anabas Testudineus Bloch) dalam Media Air Gambut yang Ditambah Pupuk Kandang Kotoran Ayam dan Kapur - Ritoasi Ritoasi; Inga Torang; Kartika Bungas (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
This study aims to determine the influence of media use the peat water of fertilizer and lime on the growth of fish seed Betok (Anabas testudineus Bloch) reared in aquarium. The experimental design used was completely randomized design (CRD) with 4 treatments and 3 replications. The results showed the highest relative growth was in treatment A (control) was (0.26%), treatment C (0.18%), Treatment B (0.13%), and treatment D (0.12%) . For the survival rate of treatment A (control) (100%), Treatment B (92%), treatment C (76%), and treatment D (46%). For the condition factor treatment A (control) (4.21), treatment B (3.77), treatment C (3.37), and treatment D (3.13). Results of water quality measurements indicate the temperature range of 25.7 to 27.9 ° C, pH ranged from 6.05 to 10.48, CO2 ranged from 6.30 to 19.98 and DO ranged between 3.06 to 7.19.